Economic Improvement of Nagari Gunuang Rajo Community, Batipuh, Tanah Datar - Kurnia Illahi Manvi; Lise Asnur; Arif Ardian; Retnaningtyas Susanti (Universitas Negeri Padang, 2020)
Nagari Gunung Rajo is an area in Batipuh Subdistrict, Tanah Datar District, West Sumatra Province which is famous for its potential of Durian fruit. This potential has not yet become a priority to be developed as a greater economic opportunity. Efforts to gain an increase in the community's economy become one of Nagari's programs, and began by collaborating with Universitas Negeri Padang through the Lembaga Penelitian dan Pengabdian Masyarakat (LP2M). The collaboration was carried out with the aim of increasing the economic opportunities of the community through a program of activities from the service team within the UNP. The research background is the potential of Nagari Gunung Rajo and the efforts to improve the economy of its people. The method used in this research is a qualitative approach with qualitative descriptive analysis techniques. Field observations and interviews with parties who have key information related to Nagari are carried out to obtain data, then are processed by sorting out all information, and are presented so that it becomes information that is easily understood by the reader. The results showed that the community was still experiencing problems in utilizing their potential. The presence of the service team from the Faculty of Tourism and hospitality UNP became one of the effective strategies in helping the community develop their potential.